2016
DOI: 10.1002/btm2.10043
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic nanoscale electrostatic particles as growth factor carriers for cartilage repair

Abstract: The efficient transport of biological therapeutic materials to target tissues within the body is critical to their efficacy. In cartilage tissue, the lack of blood vessels prevents the entry of systemically administered drugs at therapeutic levels. Within the articulating joint complex, the dense and highly charged extracellular matrix (ECM) hinders the transport of locally administered therapeutic molecules. Consequently, cartilage injury is difficult to treat and frequently results in debilitating osteoarthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…There is tremendous unmet medical need for a disease-modifying OA drug. Anabolic growth factors, such as bone morphogenetic protein 7, fibroblast growth factor 18 (FGF-18), and IGF-1, have shown potential for disease modification by decreasing chondrocyte loss and increasing matrix production in preclinical studies (12,24,(38)(39)(40). Anabolic disease-modifying strategies are particularly interesting in light of a recent finding by Heinemeier et al (41) that revealed that cartilage renewal in adults is driven by aggrecan proteoglycan synthesis, with the underlying collagen matrix exhibiting no renewal in both healthy and osteoarthritic joints (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is tremendous unmet medical need for a disease-modifying OA drug. Anabolic growth factors, such as bone morphogenetic protein 7, fibroblast growth factor 18 (FGF-18), and IGF-1, have shown potential for disease modification by decreasing chondrocyte loss and increasing matrix production in preclinical studies (12,24,(38)(39)(40). Anabolic disease-modifying strategies are particularly interesting in light of a recent finding by Heinemeier et al (41) that revealed that cartilage renewal in adults is driven by aggrecan proteoglycan synthesis, with the underlying collagen matrix exhibiting no renewal in both healthy and osteoarthritic joints (41).…”
Section: Discussionmentioning
confidence: 99%
“…Tunable surface charge is another key feature of the partially PEGylated dendrimer-drug conjugate system. Previous work in our groups has shown that positively charged nanocarriers bind and penetrate cartilage efficiently via reversible electrostatic interactions with anionic cartilage matrix proteoglycans (11,12,15). Yet, the effects of degree of charge on these delivery properties have not been thoroughly explored.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoplexes of alternating layers of anionic poly (glutamic acid) and cationic poly (arginine) were readily able to penetrate cartilage, and IGF‐1 from loaded nanoplexes was detected in the synovium 4 weeks after intra‐articular injection compared to 9 days for free IGF‐1. IGF‐1 nanoplexes ensured cartilage integrity was retained in a rat model of cartilage injury, and synovial IL‐1β levels were significantly reduced in the nanoplex‐treated animals (Shah et al, ). Cartilage can also be readily penetrated by the strongly basic protein avidin due to its electrostatic attraction to negatively charged glycosaminoglycans (GAGs).…”
Section: Disease‐specific Ecm Features For Targeted Therapiesmentioning
confidence: 97%
“…However, sustained intra-articular delivery strategies by means of drug conjugated or entrapped in hydrogels have some limitations such as (i) the chemical modification could inactivate the drug and (ii) the delayed release of a small drug is generally achieved by increasing the crosslinking of the polymer, which could not flow through a syringe and finally not match the mechanical features of the joint [ 6 ]. To contrast the short therapeutic time, decreasing the frequency of administration, thus optimizing the cartilage penetration, more injectable nanoformulations based on cationic polyelectrolyte needed to be proposed for intra-articular delivery [ 7 ].…”
Section: Introductionmentioning
confidence: 99%